R software and its use in statistical data analysis [İstatistiksel veri analizinde R yazılımı ve kullanımı] - ULUMAN MERT, MÜGE (Ankara University, 2016)
The aim of this study is two old. It aims at introducing the R software at basic level as an analysis instrument which has been widespread in recent years and offers certain advantages in comparison to other statistical packages and identifying the frequency of the use of R and other packages in research in educational sciences published within the last 5 years in Turkey in 3 academic journals covered by the SSCI. Unlike the widely used statistical packages, R is an open-source software available free of charge with a dynamic structure constantly developed with the contributions of researchers from all over the world. Such a structure allows calculation of all kinds of statistical analysis which can be used by not only researchers in scientific research process but also teachers in school practices. The study was designed in descriptive survey model. It was found out that he R software was used in only one out of 1627 articles, while SPSS and Lisrel were the most frequently used statistical packages. It can be inferred from these findings that the R software has almost no use despite the significant advantages it offers. Hence, it is recommended to realize in-service training is held at universities in order to promote the use of the R software. © 2016, Ankara University. All rights reserved.
Keywords: R cRAN; R language; R software; Statistical data analyses software